Perspective of medical students on rising violence against doctors in a Medical College of Uttarakhand: A cross-sectional study - Singh, Abhinav; Vyas, Shaili; Tripathi, Pragya; Sharma, Neha; Srivastava, Abhay; Mishra, Surabhi (Indian Journal of Community Health, 2025)
Background: Workplace violence against doctors is a rising public health concern in India, with healthcare professionals at higher risk than most other occupations. Understanding medical students’ perspectives is crucial for prevention. Objective: To assess the perspectives of MBBS undergraduates on violence against doctors and identify perceived contributing factors in a North Indian tertiary care setting. Methods: A cross-sectional study was conducted among 200 MBBS students using a pre-validated, self-administered questionnaire. Data on demographics, experiences, causes, and solutions were analysed with SPSS version 20 using descriptive statistics and chi-square tests. Results: Of 200 students (45% male, 55% female; 79% aged 21–25 years), 31.5% had experienced violence and 20.5% had witnessed it. Major perceived causes included health illiteracy (86.5%), negative media portrayal (85%), and overburdened doctors causing delays (72.5%). Most (93%) believed doctors face higher risks than other professions, and 95.5% supported stricter protective laws. Violence management training (62%) and martial arts (56%) were suggested as preventive measures, though only 16.5% were aware of existing laws. Conclusion: Medical students view workplace violence as multifactorial. Strengthening legal protections, promoting media responsibility, and integrating training on violence management, communication, and legal awareness into the curriculum may help reduce its burden.